Tinjauan Yuridis Pertanggung Jawaban Ganti Rugi Kecelakaan Kereta Api di Indonesia: Legal Review Of Train Accident Compensation Liability In Indonesia - Maicel leo; Zico Ricardo Aritonang; Lenny Maria Aritonang (Jurnal Hukum Lex Generalis, 2024)
The purpose of this study is to evaluate whether PT. Kereta Api Indonesia has carried out its responsibilities in accordance with the regulations. The methodology of this study is data obtained from case-based analysis, namely data research with a legal approach and empirical data, this study uses data sourced from social media, the internet and books. The results of the study of accidents at level crossings equipped with railroad crossings are usually caused by errors by motorcyclists or cars that cross without paying attention to the crossing. Accidents at level crossings that are not equipped with railroad crossings are often caused by negligence of crossing guards.